Nonlinear damage creep model of concrete considering the influence of temperature and its parameter variation law analysis. - Lu Wang (PLoS ONE)
In order to study the creep characteristics of concrete under different temperatures, the uniaxial creep test of concrete is carried out. On this basis, the nonlinear creep model of concrete is established by using the fractal order derivative theory. According to the characteristics of the classical creep curve and the creep equation, the calculation method of creep parameters is determined. The variation law of each creep model parameter under different stress and temperature is analyzed. The results showed that the model can well reproduce the change trend of the curve during the creep process of concrete under different temperature conditions and stress levels, indicating that the model has strong adaptability and accuracy in capturing the creep law. In the later stage of concrete creep, the accelerated creep stage is often accompanied by complex situations such as rapid accumulation of internal damage and rapid deterioration of the structure. The traditional model has limitations in the accurate description of this stage, and the new model can effectively solve this problem. Undoubtedly, it enhances its value and advantages in practical applications. The elastic modulus of the elastomer controls the instantaneous strain. The elastic modulus, viscosity coefficient and fractal order of viscoelastic body control the viscoelastic creep and creep rate. Viscosity coefficient and fractal order of viscoplastic body control the viscoplastic creep and creep rate.